Educator’s resilience in agricultural higher education system during COVID-19 pandemic: empirical evidence from Iran - Ghiasvand, Maryam; Abbasi, Enayat; Saadvandi, Mahsa; Pariab, Jaber (Frontiers in Education, 2024)
Today, educators experience complicated challenges in their job. The stress and burnout of educators has turned into a growing concern. In recent years, the challenges have been increased by the COVID-19 epidemic, and educators have been forced to use virtual methods for education in this situation. Under these conditions, the flexibility and resilience of educators can help people mostly in adaptability, increasing tolerance and optimal use of conditions for better learning. The present study is aimed to analyze the resilience of educators during the COVID-19 pandemic in Iran’s agricultural higher education system. The statistical population of the study were 3,640 educators of agricultural faculties of state universities (N = 3,640). Using the Krejcie and Morgan’s table and stratified random sampling with proportional assignment 347 educators were selected as the sample (n = 347). The data collection instrument was a researcher-made questionnaire whose validity was verified by calculating average variance extracted (AVE) and its reliability was confirmed by calculating Cronbach’s alpha and composite reliability (CR). The collected data were analyzed using structural equation modeling and Smart PLS3.3.9 software. It was found that four investigated factors, motivational-emotional, technical skill, social, and supportive factors had positive and significant relationship with the resilience behavior of educators. Among them, motivational-emotional factors had the highest effect on the educators’ resilient behavior. Based on the findings of the research, practical recommendations have been presented to enhance the educators’ resilient behavior.